2002
DOI: 10.1073/pnas.212640899
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis at a dinuclear [CuSMo(O)OH] cluster in a CO dehydrogenase resolved at 1.1-Å resolution

Abstract: The CO dehydrogenase of the eubacterium Oligotropha carboxidovorans is a 277-kDa Mo-and Cu-containing iron-sulfur flavoprotein. Here, the enzyme's active site in the oxidized or reduced state, after inactivation with potassium cyanide or with n-butylisocyanide bound to the active site, has been reinvestigated by multiple wavelength anomalous dispersion measurements at atomic resolution, electron spin resonance spectroscopy, and chemical analyses. We present evidence for a dinuclear heterometal [CuSMo(AO)OH] cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
374
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(400 citation statements)
references
References 29 publications
13
374
0
3
Order By: Relevance
“…The geometry of the molybdenum coordination sphere described here differs from that previously reported for Desulfovibrio gigas aldehyde oxididoreductase (7) and that for XOR, where, due to limited resolution of diffraction data, assignment was based on the aldehyde oxidoreductase precedent (5); the MoAS and the MoAO group have switched positions, making the oxygen the apical ligand. The geometry described here, however, is consistent with a recently refined 1.7-Å structure of the salicylatebound form of XDH (B.T.E., K.O., T.N., and E.F.P., unpublished data) and is also similar to that of a recent high-resolution (1.1-Å) structure of CO dehydrogenase, although the latter contains an additional Cu ion in its active site (28).…”
Section: Discussionsupporting
confidence: 91%
“…The geometry of the molybdenum coordination sphere described here differs from that previously reported for Desulfovibrio gigas aldehyde oxididoreductase (7) and that for XOR, where, due to limited resolution of diffraction data, assignment was based on the aldehyde oxidoreductase precedent (5); the MoAS and the MoAO group have switched positions, making the oxygen the apical ligand. The geometry described here, however, is consistent with a recently refined 1.7-Å structure of the salicylatebound form of XDH (B.T.E., K.O., T.N., and E.F.P., unpublished data) and is also similar to that of a recent high-resolution (1.1-Å) structure of CO dehydrogenase, although the latter contains an additional Cu ion in its active site (28).…”
Section: Discussionsupporting
confidence: 91%
“…Genes coding for chemolithotrophic pathways known to be associated with extreme environments (Inskeep et al, 2010;Kozubal et al, 2011), including the oxidation of ferrous iron, hydrogen, arsenic, sulfur, ammonium or methane, were not found in the NAG1 assemblies. However, the NAG1 populations have two separate loci that encode aerobic carbon monoxide (CO) dehydrogenases and associated maturases (Dobbek et al, 2002;King and Weber, 2007). One locus encodes a 'Form I' CO dehydrogenase along with coxFSM and the other contains three coxL 'Form II' CO dehydrogenase sequences along with coxDEFG (Supplementary Figures S5, S6).…”
Section: Functional Analysis Of Nag1 Genome Sequencementioning
confidence: 99%
“…Several crystal structures of other members of the family have also been determined [9][10][11][12][13][14]. The combination of structural and spectroscopic data on enzymes of this family has shown that the active site consists, in the Mo(VI) state, of a molybdenum atom in a squarepyramidal geometry that coordinates the two sulfur atoms from one pyranopterin ligand, one oxo ligand, one hydroxyl/water molecule and one sulfido ligand.…”
Section: Introductionmentioning
confidence: 99%